Gender Mainstreaming in Coastal Zoning and Its Effect on the Economic Resilience of Coastal Communities - Kasta Rosyada; Masaji Faiz Dani Agus Setiani; Merisa Dwi Juanita (MUWAZAH : jurnal kajian gender, 2022)
Women’s contributions and roles in coastal communities are frequently overlooked. Through a gender-based empowerment strategy, gender-based coastal zoning can result in an integrated and long-lasting implementation of coastal area management and increase coastal community resilience. This paper aims to emphasize the need of considering the demands and behaviors of women and to determine the effect of gender mainstreaming in coastal zoning on coastal area resilience. The method used in this paper is descriptive research as to conduct the potential for conducting analysis related to the role of women in coastal areas, the tools used by researchers is zoning method based on the results of the literature study, the trend of gender involvement in coastal and marine areas is still dominated by men (64%) and women (36%). The findings in this study shows Both women and men have different roles and it is undeniable that they are still interrelated in exploring fishery and marine resources. The economic resilience of coastal communities (fishers) is highly dependent on the presence of fish. The existence of fish is highly dependent on the presence of coral reefs, mangrove forests, and non-mangrove forests or coastal forests as green belts. There is a causal relationship between fish and their environment, the role of women in coastal areas is mostly found in inland coastal areas with the types of activities of production, product processing, marketing, and resources collection, the efforts to close the gap are to use the use of marine spatial planning by defining the use of space and traditional user rights through the participation of women to make them more empowered.